2018
DOI: 10.1371/journal.pone.0193814
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of gemcitabine in brief versus prolonged low-dose infusion for advanced non-small cell lung cancer

Abstract: ObjectiveTo evaluate the efficacy and safety of gemcitabine (GEM) at 30 min standard-dose infusion (30 min-SDI) compared with prolonged low-dose infusion (P-LDI) in patients with advanced non-small-cell lung cancer (NSCLC).MethodsElectronic databases including Pubmed, EMbase, Cochrane Library, CNKI, CBM, and VIP were searched using keywords “GEM”, “P-LDI”, and “NSCLC”. Review Manager 5.3 was used to perform the meta-analysis. Primary endpoints were overall response rate (ORR) and 1-year survival rate (1-year S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Multiple small underpowered studies prior to ours have tried to address this question and a recent meta analysis of these studies suggested that low dose gemcitabine with prolonged infusion leads to a similar 1 year OS and has a lower rate of leukopenia and thrombocytopenia [12], [13], [14], [20], [21], [22], [23]. However, the authors had cautioned that the evidence was of low quality and a high quality large trial was required to answer this question and to test the validity of their results.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple small underpowered studies prior to ours have tried to address this question and a recent meta analysis of these studies suggested that low dose gemcitabine with prolonged infusion leads to a similar 1 year OS and has a lower rate of leukopenia and thrombocytopenia [12], [13], [14], [20], [21], [22], [23]. However, the authors had cautioned that the evidence was of low quality and a high quality large trial was required to answer this question and to test the validity of their results.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, oral gemcitabine administration would allow for greater flexibility in designing dosing schedules, enabling both metronomic gemcitabine dosing (i.e., frequent low dose administration) and dosing which replicates gemcitabine pharmacokinetics following a prolonged intravenous infusion. There is evidence that such dosing schedules may lead to improvements in efficacy and/or reductions in toxicity [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, Gem administered as a 30-min infusion of 1,000–1,250 mg/m 2 is the standard regimen. However, several trials 9 – 12 have demonstrated that another type of administration [prolonged low-dose infusion (P-LDI)] exhibits a comparable activity and toxicity compared with a 30-min infusion of the standard dose (30-min SDI). Previously, we suggested that P-LDI was superior in terms of the overall response rate, experienced less grade 3/4 thrombocytopenia and leukopenia compared with 30-min SDI, and could be a viable treatment option for advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we suggested that P-LDI was superior in terms of the overall response rate, experienced less grade 3/4 thrombocytopenia and leukopenia compared with 30-min SDI, and could be a viable treatment option for advanced NSCLC. 9 However, whether the same is also applicable to other cancer types remains unclear. Hence, this systematic review of the current literature aims to provide some references for Gem administered as a prolonged infusion and supports the need for further investigation regarding both clinical efficiency and safety.…”
Section: Introductionmentioning
confidence: 99%